Water in our mouth: food metaphors in the Portuguese language - Martins, Cláudia (2018)
This article intends to demystify the conventional approach to metaphors, which have been traditionally regarded as a mere poetic and imaginative device, as well a means for rhetorical flourish. In order to achieve this purpose, we focus on some basic considerations about figurative language (versus literal language) and the tropes, namely the simile, the synecdoche and the metonymy. From this, we introduce the approach of cognitive linguistics, especially that represented by Lakoff & Johnson (1980), that highlights the importance of metaphors in structuring and organising our thoughts and actions, enabling at the same time to understand extralinguistic reality. Having established the theoretical context, we put forth a set of metaphorical expressions in Portuguese, related to the conceptual domain of food, which are analysed in terms of their meaning and the identification of their underlying metaphor and are provided with a context taken from the Portuguese newspaper Público. Therefore, we aim at proving that even the most basic of areas of life, such as food, are fraught with metaphors.